Question
upstudy study bank question image url

Solve the quadratic equation. \[ 7 x^{2}+3 x-1=0 \] Write one exact, simplified solution in each box. You can add or remove boxes. If a solution not a real number, write it in the form a + bi or a - bi, where a and b are real numbers. \begin{tabular}{|c}\( \square \frac{\square}{\square} \)\end{tabular}

Ask by Nunez Ball. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solutions are: \[ x_{1} = -\frac{3 + \sqrt{37}}{14} \] \[ x_{2} = \frac{-3 + \sqrt{37}}{14} \]

Solution

Solve the equation \( 7x^2+3x-1=0 \). Solve the quadratic equation by following steps: - step0: Solve using the quadratic formula: \(7x^{2}+3x-1=0\) - step1: Solve using the quadratic formula: \(x=\frac{-3\pm \sqrt{3^{2}-4\times 7\left(-1\right)}}{2\times 7}\) - step2: Simplify the expression: \(x=\frac{-3\pm \sqrt{3^{2}-4\times 7\left(-1\right)}}{14}\) - step3: Simplify the expression: \(x=\frac{-3\pm \sqrt{37}}{14}\) - step4: Separate into possible cases: \(\begin{align}&x=\frac{-3+\sqrt{37}}{14}\\&x=\frac{-3-\sqrt{37}}{14}\end{align}\) - step5: Rewrite the fraction: \(\begin{align}&x=\frac{-3+\sqrt{37}}{14}\\&x=-\frac{3+\sqrt{37}}{14}\end{align}\) - step6: Rewrite: \(x_{1}=-\frac{3+\sqrt{37}}{14},x_{2}=\frac{-3+\sqrt{37}}{14}\) The solutions to the quadratic equation \(7x^2 + 3x - 1 = 0\) are: \[ x_{1} = -\frac{3 + \sqrt{37}}{14} \] \[ x_{2} = \frac{-3 + \sqrt{37}}{14} \] Therefore, the exact, simplified solutions are: \[ x_{1} = -\frac{3 + \sqrt{37}}{14} \] \[ x_{2} = \frac{-3 + \sqrt{37}}{14} \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the quadratic equation \( 7x^{2}+3x-1=0 \) using the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), we identify \( a = 7 \), \( b = 3 \), and \( c = -1 \). Calculating the discriminant: \[ b^2 - 4ac = 3^2 - 4(7)(-1) = 9 + 28 = 37 \] Now applying the formula: \[ x = \frac{-3 \pm \sqrt{37}}{2 \times 7} = \frac{-3 \pm \sqrt{37}}{14} \] Thus, the two exact, simplified solutions are: \[ \begin{tabular}{|c}\(\square \frac{-3 + \sqrt{37}}{14}\)\\ \(\square \frac{-3 - \sqrt{37}}{14}\)\end{tabular} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy